Synthesis, characterization and corrosion inhibition efficiency of N-(4-(Morpholinomethyl Carbamoyl Phenyl) Furan-2-Carboxamide - N. Zulfareen; K. Kannan; T. Venugopal; S. Gnanavel (Arabian Journal of Chemistry, 2016)
A mannich base namely N-(4-(Morpholinomethyl Carbamoyl Phenyl) Furan-2-Carboxamide (MFC) was synthesized and characterized by FT-IR, 1H NMR, and 13C NMR. The molecular weight of MFC was confirmed by LC-MS. The inhibition effect of MFC on brass in 1 M HCl medium has been investigated by weight loss measurement, potentiodynamic polarization, electrochemical impedance spectroscopy (EIS) and cyclic voltametry (CV). Thermodynamic parameters such as free energy, entropy and enthalpy were calculated to describe the mechanism of corrosion inhibitor. The inhibition efficiency of MFC increases with increase in concentration and temperature ranges from 30 °C to 60 °C. Polarization measurements indicated that MFC acts as a mixed type corrosion inhibitor. AC impedance indicates that Rct value increases with increase in the concentration of inhibitor. CV reveals that the oxidation of the copper is controlled by the addition of inhibitor on the brass metal. Surface analysis using scanning electron microscope (SEM) shows a significant morphological improvement on the brass surface with the addition of the inhibitor. The adsorption of MFC on brass obeys Langmuir adsorption isotherm. The molecular structure of MFC was distorted to quantum chemical indices using density functional theory (DFT) which indicates that the inhibition efficiency of MFC is closely related to quantum parameters.